What we already know about corporate digital responsibility in IS research: A review and conceptualization of potential CDR activities - K. Valerie Carl; Oliver Hinz (Electronic Markets, 2024)
Advances in new technologies affect private and professional lives alike, posing new opportunities and threats for companies, consumers, and society. In this context, the concept of corporate digital responsibility (CDR) gains traction enabling technologies benefitting humanity while exceeding mere technology advancements. Yet, theory and practice still lack a systematic in-depth understanding of the concept's scope up to concrete activities. The aim of this paper is to enable a more concrete and deeper understanding of the concept scope by drawing on available knowledge in the thematically related discipline of information systems (IS) in general and electronic markets in particular. The study employs an extended systematic literature review to aggregate prior knowledge in this research domain relatable to the concept of CDR and to develop an in-depth classification of potential CDR activities inductively according to ten dimensions, corresponding sub-dimensions, and respective fields of action. This contributes to the overarching goal to develop the conceptualization of CDR and to anchor the concept in the context of electronic markets, thereby fostering human and social value creation.
Keywords: L00; O30; 620; Corporate digital responsibility; Conceptualization; Extended systematic literature review; Grounded theory literature-review method; Electronic markets; Information systems research